POLA PENGGUNAAN TIK (TEKNOLOGI INFORMASI DAN KOMUNIKASI) DAN PENINGKATAN EKONOMI MASYARAKAT DESA - Imran, Hasyim Ali (Jurnal Insani, 2017)
This paper basically intersects the problem that aims to throw a discourse about research concerning the use of ICT (Information and Communication Technology) and economic improvement of society. Because of limited discourse, therefore for enthusiasts the same problem could be widen the phenomenon referred to the wider problem or further minimize it. In addition, the method proposed in this research is also limited to one method, namely the method based on the positivistic research paradigm with the survey method. Researchers interested in the same problem may be creative in conducting similar research with different research paradigms, for example interpretive research paradigms with case study research methods. So with the discourse that surfaced from the results of discussion in this paper, is expected to emerge new creativities.